BENCHMARKING ANALYSIS FOR CASCARA DEVELOPMENT STRATEGY AT CHARISMA CHARITA MSMEs (MICRO, SMALL, MEDIUM, ENTERPRISES) IN CENTRAL ACEH REGENCY - Tri Arini Utami; Fadli Fadli; Martina Martina (Jurnal Mahasiswa Agribisnis, 2023)
Charisma Charita MSMEs (Micro, Small, Medium, Enterprises) is a business that produces coffee husk product cascara, which is located in Berawang Dewal Village, Jagot Jeget District, Central Aceh Regency. The production of cascara in Charisma Charita is still low because it is not widely known by the public and product innovation is still minimal, especially in terms of variants, packaging and size. In addition, the promotion is also not optimal so the revenue obtained is still low. This research aims to conduct xagainst similar competitors to find competitive advantages, then formulating development strategies using SWOT analysis. Based on the results of the IFE and EFE matrix analysis, it showed that Charisma Charita MSMEs is in quadrant III position which focuses on the W-O (Weakness-Opportunity) strategy and resulting 6 alternative strategies. Keywords: Benchmarking, Cascara, Development Strategy, SWOT.